The complete visible human : the complete high-resolution male and female datasets from the visible human project TM - Peitgen, Heinz-Otto; Berghorn, Wilhelm; Biel, Matthias (Springer, 1998)
2 CD-ROMy obsahují kompletní anatomické příčné řezy muže (VisMan) a ženy (VisWom)
Keywords: Anatomy, Cross-Sectional; Anatomy; anatomie průřezová; anatomie